In situ construction of Bi5O7I/Bi4Ti3O12 heterostructure composites with plentiful phase interfaces for the boosted selective oxidation of benzylic alcohols under visible light. Issue 38 (10th September 2021) - Wang, Jingchao; Li, Siyi; Yang, Kunlong; Zhang, Tianyong; Jiang, Shuang; Li, Xianggao; Li, Bin
Abstract : The novel Z-scheme flower-like Bi5 O7 I/Bi4 Ti3 O12 composites were prepared via in-situ grown under hydrothermal-calcination method, which were exhibited outstanding photocatalytic performance for selective oxidation of benzylic alcohols. Abstract : Novel flower-like Bi5 O7 I/Bi4 Ti3 O12 (BOI/BTO) photocatalysts were successfully designed and fabricated by an in situ growth method. The BOI and BTO in BOI/BTO composites have abundant interface contact and constructed a Z-scheme heterojunction structure. Therefore, these composites exhibited excellent performance for the selective oxidation of benzylic alcohols under visible light. It was attributed to the stronger absorption capacity of visible light and the high separation efficiency of photogenerated carriers via the Z-scheme transfer mechanism; especially, the sample BOI/BTO-1.5 achieved 92.4% selectivity for the oxidation of 4-methylbenzyl alcohol (4-MBA) to 4-methyl-benzaldehyde (4-MBAD) in the presence of H2 O2, which also exhibited good stability, reusability and substrate adaptability. As evidenced by the activity experiments, trapping experiments and ESR analysis, the ˙O2 − radicals and HOO˙ radicals were supposed to be the main active species directly involved in the photocatalytic oxidation process. Based on the optical and electrical analysis, a Z-scheme transfer facilitated mechanism of photocatalytic selective oxidation of benzylic alcohols was speculated.